2021
DOI: 10.1007/s11912-021-01138-3
|View full text |Cite
|
Sign up to set email alerts
|

Adult T-Cell Leukemia: a Comprehensive Overview on Current and Promising Treatment Modalities

Abstract: Purpose of the ReviewAdult T-cell leukemia (ATL) is an aggressive chemo-resistant malignancy secondary to HTLV-1 retrovirus. Prognosis of ATL remains dismal. Herein, we emphasized on the current ATL treatment modalities and their drawbacks, and opened up on promising targeted therapies with special focus on the HTLV-1 regulatory proteins Tax and HBZ. Recent Findings Indolent ATL and a fraction of acute ATL exhibit long-term survival following antiviral treatment with zidovudine and interferon-alpha. Monoclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 136 publications
0
14
0
Order By: Relevance
“…In conclusion, our results pinpoint that ATL is not only a virus-initiated leukemia, but also a virus-addicted malignancy, providing a strong rationale for the clinical development of Tax- targeting therapy [ 64 ]. Potential candidates include IFN and ATO which induce Tax degradation by the proteasome [ 17 , 37 42 ], anti-Tax immunotherapy [ 33 ] including therapeutic vaccines [ 36 ], allogeneic stem cell transplantation through Tax-specific CTL [ 65 ], or chimeric antigen receptor (CAT) T or natural killer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our results pinpoint that ATL is not only a virus-initiated leukemia, but also a virus-addicted malignancy, providing a strong rationale for the clinical development of Tax- targeting therapy [ 64 ]. Potential candidates include IFN and ATO which induce Tax degradation by the proteasome [ 17 , 37 42 ], anti-Tax immunotherapy [ 33 ] including therapeutic vaccines [ 36 ], allogeneic stem cell transplantation through Tax-specific CTL [ 65 ], or chimeric antigen receptor (CAT) T or natural killer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Adult T-cell leukemia (ATL) is an aggressive drug-resistant hematological malignancy tumor secondary to HTLV-1 retrovirus infection ( 37 ). The prevalence of HTLV-1 is mainly attributed to vertical transmission via breast feeding.…”
Section: Fhl3 In Adult T-cell Leukemiamentioning
confidence: 99%
“…In addition, we reported that V. virgatum leaves prevent the proliferation of adult T-cell leukemia (ATL) cells [ 12 , 13 ]. ATL is an aggressive chemotherapy-resistant malignancy secondary to infection with the retrovirus human T-cell leukemia virus type 1 (HTLV-1) [ 14 ]. Based on these studies, agricultural efforts have focused on breeding V. virgatum leaves for use as green tea, although the leaves have not previously been used as a food ingredient.…”
Section: Introductionmentioning
confidence: 99%